A survey of the flora and fauna of mangrove forests in Bachok, Kelantan, Malaysia - Sasekumar, A.; Moh, H.H. (Faculty of Science, University of Malaya, 2010)
The flora and fauna of mangrove forests in nine localities in Bachok, Kelantan were investigated from 16th to 19th June 2008. Though much of the mangroves have been reclaimed, remnant mangroves were found in the estuary of Semerak River. Nypa fruticans colonized the banks of the estuary, while Rhizophora apiculata dominated much of the upper shore. Elsewhere, there were small stands of Sonneratia alba, Avicennia marina and Bruguiera spp. The benthic fauna was dominated by 18 species of gastropods, 5 species of bivalves, 13 species of crustaceans (mostly sesarmine crabs), a sipuncula and 3 species of small fishes. East coast mangroves are estuarine in nature as they are located in sheltered situations, and thus not subjected to strong wave action or tidal currents. Accumulation of leaf litter on the forest floor seems to have encouraged high numbers of detritus feeding gastropod, Neritina violacea, to flourish in the high shore mangrove forest.